The LISN database: description and initial results - De la Jara, César (2009)
The heavy volume of data that GPS, ionosondes and magnetometers are continuously collecting is stored in the LISN server and managed using a set of rules that are intended to provide an efficiently way to manipulate the large data sets and also implement an adequate method to systematically transform all this information into knowledge. LISN integrates multiple data sources and should provide security, integrity and availability in a multi-user environment. Data from the remote stations arrives to the server continuously and is stored, processed and distributed. This data is easily available and in some cases freely accessible to the community promoting research and encouraging collaboration between users.